Encapsulation film, composite glass and photovoltaic building integrated components
By using a three-layer structure encapsulating film in safety glass, the problems of poor aging reliability and complex composite film technology of safety glass are solved, and high strength, excellent light transmittance and low cost effects are achieved.
Patent Information
- Application Number
- CN202310012623.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-01-05
AI Technical Summary
In the prior art, safety glass has poor long-term aging reliability, complex composite sheet technology, low yield and high cost.
An encapsulating adhesive film is provided, including a first bonding layer, a reinforcement layer and a second bonding layer that are stacked in sequence, and the reinforcement layer consists of a matrix resin and an active agent dispersed therein, by controlling the structure and active agent of the matrix resin. The choice is to improve the strength and light transmittance of the adhesive film.
It achieves excellent long-term aging reliability of safety glass, simple composite sheet technology, high yield and low cost, and meets the requirements of safety glass.
Smart Images

Figure CN116285725B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optoelectronic technology, and in particular to a packaging adhesive film, composite glass and photovoltaic building integrated components. Background Art
[0002] In China, carbon dioxide emissions caused by building energy consumption now account for about 1 / 4 of China's total carbon dioxide emissions. With the advancement of urbanization, the increase in the proportion of the service industry in the national economy and the improvement of people's living standards, building energy consumption will further increase. In order to achieve the "dual carbon goals", it is imperative to reduce building energy consumption. Photovoltaic building integration (BIPV) is to install photovoltaic modules as part of the building on the periphery of the building, so that the building can generate electricity and truly achieve green buildings, which will greatly reduce building carbon emissions. However, the photovoltaic modules used for BIPV, in addition to meeting the aging requirements of photovoltaic modules, also need to meet the safety requirements of the construction industry. At present, the traditional packaging materials of photovoltaic modules, EVA or POE, cannot meet the use standards of building safety glass due to insufficient material strength, and the safety performance (such as anti-falling ball penetration, anti-shotbag impact, etc.) cannot meet the application field of photovoltaic modules. At present, BIPV modules can only be encapsulated with PVB. However, PVB has a high moisture content and poor weather resistance, which cannot meet the requirements of long-term and efficient operation of modules.
[0003] In addition to BIPV, the laminated materials used in safety glass in other construction industries and automotive safety glass are all PVB. Although PVB has good safety performance, it has poor adhesion to glass and is prone to debonding after lamination. It requires the use of an autoclave lamination process, which is complex and inefficient, with high equipment costs, high defective rate after lamination, and high rework rate. Therefore, a new type of high-strength material is needed that has good adhesion to glass and long-term reliability and can meet the requirements for the use of safety glass. Summary of the invention
[0004] The main purpose of the present invention is to provide an encapsulation film, composite glass and photovoltaic building integrated components to solve the problems of poor long-term aging reliability, complex assembly process, low yield and high cost of safety glass in the prior art.
[0005] In order to achieve the above object, according to one aspect of the present invention, a packaging film is provided, which includes a first adhesive layer, a reinforcement layer and a second adhesive layer stacked in sequence, wherein the reinforcement layer includes a matrix resin and an active agent dispersed therein; the structural formula of the matrix resin is as follows:
[0006]
[0007] in,
[0008]
[0009] and 65%≤a≤95%, 15%≤b≤80%; R1 and R2 are each independently selected from H, substituted or unsubstituted C1~C 10 Alkyl; M n+ It is a metal ion, n is 1 or 2; the active agent contains at least two active groups that can react with -COOH.
[0010] Furthermore, the above R1 and R2 are each independently selected from H, a substituted or unsubstituted alkyl group of C1 to C6; preferably, R1 and R2 are each independently selected from any one or more of H, methyl, ethyl, propyl, isopropyl, pentyl, and hexyl; further, preferably, R1 and R2 are each independently selected from any one of H, methyl or ethyl.
[0011] Furthermore, the active group of the above-mentioned active agent is selected from any one or more of hydroxyl, amino, thiol, and acyl chloride. Preferably, the active agent is selected from any one or more of ethylene glycol, 1,2-butanediol, ethylenediamine, and adipoyl chloride.
[0012] Furthermore, the above M n+ Selected from Na + , K + 、Zn 2+ Any one of multiple types.
[0013] Furthermore, if
[0014] Furthermore, the light transmittance of the reinforcement layer is greater than 85%, the thickness of the reinforcement layer is preferably between 0.10 and 0.55 mm, and the melting point of the matrix resin is preferably between 80 and 110°C.
[0015] Further, the thickness of the first adhesive layer and the second adhesive layer is independently 0.05-0.4 mm. In parts by weight, the first adhesive layer and the second adhesive layer independently include: 100 parts by weight of base resin: 0.1-2 parts by weight of initiator; 0.2-2 parts by weight of bridging agent; 0.05-1 parts by weight of silane coupling agent; preferably, the base resin is selected from any one or more of ethylene vinyl acetate copolymer, ethylene propylene copolymer, ethylene butene copolymer, ethylene pentene copolymer, ethylene hexene copolymer, and ethylene octene copolymer; preferably, the initiator is selected from tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1, Any one or more of 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-amyl peroxy 2-ethylhexyl carbonate, 2,5-dimethyl 2,5-dimethyl 2,5-dimethyl 2,5-bis(benzoylperoxy)-hexane, tert-amyl peroxycarbonate, tert-butyl peroxy 3,3,5-trimethylhexanoate, azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptonitrile, dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, azobisisobutylimidazole hydrochloride, azoisobutylcyanoformamide The preferred bridging agent is selected from triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, 2,4,6-tris(2-propenyloxy)-1,3,5-triazine, tricyclohexane dimethanol diacrylate Any one or more of ester, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, and polyethylene glycol dimethacrylate; preferably, the silane coupling agent is selected from any one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxide tert-butyl silane, vinyl triacetoxysilane, vinyl tri(β-methoxyethoxy) silane, γ-aminopropyl triethoxysilane, γ-methacryloyloxypropyl trimethoxysilane, γ-glycidyl ether oxygen propyl trimethylsilane, and 3-aminopropyl trimethylsilane.
[0016] Furthermore, the first bonding layer and the second bonding layer each independently include 0.5 to 20 parts of a pigment, preferably the pigment is selected from any one or more of titanium dioxide, carbon black, copper chrome black, iron red, and iron yellow; preferably, the first bonding layer and the second bonding layer each independently include 0.5 to 2 parts of an ultraviolet absorber.
[0017] According to another aspect of the present invention, a composite glass is provided, comprising a first glass, an adhesive film and a second glass stacked in sequence, wherein the adhesive film is selected from the above-mentioned encapsulation adhesive film.
[0018] According to another aspect of the present invention, a photovoltaic building integrated assembly is provided, comprising a packaging film, wherein the packaging film is the aforementioned packaging film.
[0019] By applying the technical solution of the present invention, in the packaging film of the present application having the above three-layer structure, since the value of a is too high, the strength of the packaging film is too low, the transmittance is low and the haze is large, and the value of a is too low, the strength of the packaging film melt is too high and it is not easy to process. If the value of b is too high, the tear resistance of the packaging film will be reduced, and if the value of b is too low, the tensile strength of the packaging film will be affected. Therefore, controlling the values of a and b within the above range can not only ensure its adhesion, but also ensure that it has high strength and transmittance, thereby meeting the use requirements of safety glass. In addition, during high-temperature lamination or lamination, the active agent reacts with the carboxyl group in the matrix resin, which is beneficial to further improve the strength of the reinforcement layer. At the same time, the safety glass including the packaging film has excellent long-term aging reliability, simple lamination process, high yield and low cost. DETAILED DESCRIPTION
[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0021] As analyzed in the background technology, the safety glass in the prior art has the problems of poor long-term aging reliability, complex assembly process, low yield and high cost. To solve this problem, the present invention provides a packaging film, composite glass and photovoltaic building integrated assembly.
[0022] In a typical embodiment of the present application, a packaging film is provided, which includes a first adhesive layer, a reinforcement layer, and a second adhesive layer stacked in sequence, wherein the reinforcement layer includes a base resin and an active agent dispersed therein; the structural formula of the base resin is as follows:
[0023]
[0024] in,
[0025]
[0026] and 65%≤a≤95%, 15%≤b≤80%; R1 and R2 are each independently selected from H, substituted or unsubstituted C1~C 10 Alkyl; M n+ It is a metal ion, n is 1 or 2; the active agent contains at least two active groups that can react with -COOH.
[0027] In the packaging film with the above three-layer structure of the present application, since the value of a is too high, the strength of the packaging film is too low, the transmittance is low and the haze is large, and the value of a is too low, the strength of the packaging film melt is too high and it is not easy to process. If the value of b is too high, the tear resistance of the packaging film will be reduced, and if the value of b is too low, the tensile strength of the packaging film will be affected. Therefore, controlling the values of a and b within the above range can not only ensure its adhesion, but also ensure that it has high strength and transmittance, thereby meeting the use requirements of safety glass. In addition, during high-temperature lamination or lamination, the active agent reacts with the carboxyl group in the matrix resin, which is beneficial to further improve the strength of the reinforcement layer. At the same time, the safety glass including the packaging film has excellent long-term aging reliability, simple lamination process, high yield and low cost.
[0028] In one embodiment of the present application, the above R1 and R2 are each independently selected from H, a substituted or unsubstituted alkyl group of C1 to C6; preferably, R1 and R2 are each independently selected from any one or more of H, methyl, ethyl, propyl, isopropyl, pentyl, and hexyl; further, preferably, R1 and R2 are each independently selected from any one of H, methyl or ethyl.
[0029] The above-mentioned preferred substituents are more conducive to reducing the gaps between the molecular chains of the matrix resin and improving its strength.
[0030] Preferably, the active group of the above-mentioned active agent is selected from any one or more of hydroxyl, amino, thiol, and acyl chloride, and preferably the active agent is selected from any one or more of ethylene glycol, 1,2-butanediol, ethylenediamine, and adipoyl chloride. This helps to improve the reaction between it and the matrix resin, obtain a network polymer, and further improve the strength of the matrix resin.
[0031] Preferably the above M n+ Selected from Na + , K + 、Zn 2+ Any one or more of the above can help to improve the strength of the matrix resin while maintaining the high light transmittance of the matrix resin as much as possible.
[0032] If preferred Then 0.1≤c≤10, which helps to control the polymerization degree of the exposed carboxyl groups in the matrix resin and thus improve its strength.
[0033] In one embodiment of the present application, the light transmittance of the above-mentioned reinforcement layer is greater than 85%, the thickness of the reinforcement layer is preferably between 0.10 and 0.55 mm, and the melting point of the matrix resin is preferably between 80 and 110°C.
[0034] Controlling the thickness and transmittance of the above-mentioned reinforcing layer helps to obtain a reinforcing layer with excellent comprehensive transmittance and strength properties. Controlling the melting point of the matrix resin within the above-mentioned range helps to ensure that the glass remains in a solid state at the temperature in the use environment, thereby ensuring its strength.
[0035] In one embodiment of the present application, the thickness of the first bonding layer and the second bonding layer is independently 0.05-0.4 mm. In parts by weight, the first bonding layer and the second bonding layer independently include 100 parts by weight of a base resin, 0.1-2 parts by weight of an initiator, 0.2-2 parts by weight of a bridging agent, and 0.05-1 parts by weight of a silane coupling agent; preferably, the base resin is selected from any one or more of ethylene vinyl acetate copolymer, ethylene propylene copolymer, ethylene butene copolymer, ethylene pentene copolymer, ethylene hexene copolymer, and ethylene octene copolymer, and the initiator is selected from tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethyl any one of tert-butylperoxy)-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, 2,5-dimethyl-2,5-dimethyl-2,5-dimethyl-2,5-bis(benzoylperoxy)-hexane, tert-amyl peroxy carbonate, tert-butyl peroxy-3,3,5-trimethylhexanoate, azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptylonitrile, dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride, and azoisobutylcyanoformamide or more, preferably the bridging agent is selected from triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, 2,4,6-tris(2-propenyloxy)-1,3,5-triazine, tricyclohexane dimethanol dipropylene glycol Any one or more of acrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, and polyethylene glycol dimethacrylate, and the silane coupling agent is preferably selected from any one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxide tert-butyl silane, vinyl triacetoxysilane, vinyl tri(β-methoxyethoxy) silane, γ-aminopropyl triethoxysilane, γ-methacryloyloxypropyl trimethoxysilane, γ-glycidyl ether oxygen propyl trimethyl silane, and 3-aminopropyl trimethyl silane.
[0036] Preferably, the first adhesive layer and the second adhesive layer described above help to improve the adhesiveness of the packaging film, thereby ensuring its adhesiveness with the glass.
[0037] In one embodiment of the present application, the above-mentioned first bonding layer and the second bonding layer each independently include 0.5 to 20 parts of a pigment, preferably the pigment is selected from any one or more of titanium dioxide, carbon black, copper chrome black, iron red, and iron yellow; preferably, the first bonding layer and the second bonding layer each independently include 0.5 to 2 parts of an ultraviolet absorber.
[0038] Preferably, the first adhesive layer and the second adhesive layer allow the reinforcing layer to have richer colors, so that the composite glass can better meet visual needs. Preferably, the inclusion of an ultraviolet absorber helps to further improve the light transmittance of the reinforcing layer.
[0039] In another typical embodiment of the present application, a composite glass is provided, comprising a first glass, an adhesive film, and a second glass stacked in sequence, wherein the adhesive film is selected from the aforementioned encapsulation adhesive film.
[0040] The composite glass including the above encapsulation film has higher safety and higher light transmittance.
[0041] In another typical embodiment of the present application, a photovoltaic building integrated component is provided, comprising a packaging film, which is the aforementioned packaging film.
[0042] The photovoltaic building integrated components including the above encapsulation films have excellent safety and service life, as well as high photoelectric conversion efficiency.
[0043] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0044] Example 1
[0045] A packaging film comprises a middle reinforcement layer and a first bonding layer and a second bonding layer located on both sides of the reinforcement layer, wherein the thickness of the reinforcement layer is 0.36 mm, the thickness of the first bonding layer is 0.2 mm, and the thickness of the second bonding layer is 0.2 mm. The composition ratio of each layer is as follows:
[0046] Table 1
[0047]
[0048] Table 2
[0049]
[0050] The structural formula of the matrix resin in the reinforcement layer is Wherein, R1 is a hydrogen atom, R2 is a methyl group, a is 0.8, b is 0.6, c is 3, M n+ for Na + , the active agent is ethylene glycol.
[0051] Example 2
[0052] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, a is 0.65.
[0053] Example 3
[0054] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, a is 0.95.
[0055] Example 4
[0056] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, b is 0.15.
[0057] Example 5
[0058] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, b is 0.8.
[0059] Example 6
[0060] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, c is 0.1.
[0061] Example 7
[0062] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, c is 10.
[0063] Example 8
[0064] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, c is 12.
[0065] Example 9
[0066] The difference from Example 1 is that the active agent in the reinforcing layer is ethylenediamine.
[0067] Example 10
[0068] The difference from Example 1 is that the thickness of the reinforcing layer is 0.10 mm, and the thickness of the first adhesive layer and the second adhesive layer are each independently 0.05 mm.
[0069] Embodiment 11
[0070] The difference from Example 1 is that the thickness of the reinforcing layer is 0.55 mm, and the thickness of the first adhesive layer and the second adhesive layer are each independently 0.4 mm.
[0071] Example 12
[0072] The difference from Example 1 is that
[0073] Table 3
[0074]
[0075]
[0076] Embodiment 13
[0077] The difference from Example 1 is that
[0078] Table 4
[0079]
[0080] Embodiment 14
[0081] The difference from Example 1 is that the initiator in the first adhesive layer is 2,2-bis(tert-butylperoxy)butane.
[0082] Embodiment 15
[0083] The difference from Example 1 is that the bridging agent in the first bonding layer is trimethylolpropane triacrylate.
[0084] Example 16
[0085] The difference from Example 1 is that the coupling agent in the first bonding layer is vinyltrimethoxysilane.
[0086] Embodiment 17
[0087] The difference from Example 1 is that the first adhesive layer and the second adhesive layer further include 10 parts of iron red respectively; the first adhesive layer and the second adhesive layer further include 1 part of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole ultraviolet absorber respectively.
[0088] Embodiment 18
[0089] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcing layer, R1 is a methyl group, R2 is an ethyl group,
[0090] Comparative Example 1
[0091] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, a is 0.5.
[0092] Comparative Example 2
[0093] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, a is 1, that is, the matrix resin is polyethylene.
[0094] Comparative Example 3
[0095] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, b is 0.1.
[0096] Comparative Example 4
[0097] The difference from Example 1 is that in the structural formula of the matrix resin in the reinforcement layer, b is 1, that is, there is no carboxyl group in the matrix resin.
[0098] Comparative Example 5
[0099] The difference from Example 1 is that there are only adhesive layer 1 and adhesive layer 2, but no reinforcing layer.
[0100] Performance Testing
[0101] The performance of the encapsulation films prepared by the above Examples 1 to 18 and Comparative Examples 1 to 5 was evaluated by the following test methods, and the test results are listed in Table 5.
[0102] 1. Transmittance and haze: The test is carried out according to GB / T 2410-2008, and the transmittance and haze of the film in the visible light band of 400-700nm wavelength are measured using a UV-visible spectrophotometer.
[0103] 2. Adhesion of glass: The test method refers to the standard GB / T 29848 "Ethylene-vinyl acetate copolymer (EVA) film for photovoltaic module encapsulation".
[0104] 3. Maximum drop height: stack and laminate glass in the order of glass + encapsulation film + glass, and then test according to Article 7:11 of GB15763.3-2009 "Architectural Safety Glass Part 3: Laminated Glass" and record the maximum drop height that meets the requirements.
[0105] Table 5
[0106]
[0107]
[0108] Compared with Example 1 and Example 12, Example 13 leads to slightly higher cost. Example 17 can meet the requirements of the packaging film with color, that is, it meets the requirements of appearance, but the photoelectric conversion efficiency is relatively low.
[0109] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0110] In the packaging film with the above three-layer structure of the present application, since the value of a is too high, the strength of the packaging film is too low, the transmittance is low and the haze is large, and the value of a is too low, the strength of the packaging film melt is too high and it is not easy to process. If the value of b is too high, the tear resistance of the packaging film will be reduced, and if the value of b is too low, the tensile strength of the packaging film will be affected. Therefore, controlling the values of a and b within the above range can not only ensure its adhesion, but also ensure that it has high strength and transmittance, thereby meeting the use requirements of safety glass. In addition, during high-temperature lamination or lamination, the active agent reacts with the carboxyl group in the matrix resin, which is beneficial to further improve the strength of the reinforcement layer. At the same time, the safety glass including the packaging film has excellent long-term aging reliability, simple lamination process, high yield and low cost.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A packaging film, characterized in that: The packaging film comprises a first adhesive layer, a reinforcement layer and a second adhesive layer stacked in sequence. Wherein, the reinforcing layer comprises a matrix resin and an active agent dispersed therein; The structural formula of the base resin is as follows: ; in, ; ; And 65%≤a≤95%, 15%≤b≤80%; R1 and R2 are each independently selected from H, substituted or unsubstituted C1~C 10 The alkyl group; M n+ is a metal ion, n is 1; The active agent contains at least two active groups that can react with -COOH, and the active groups of the active agent are selected from any one or more of hydroxyl, amino, thiol, and acyl chloride; in, ; And 0.1≤c≤10.
2. The packaging film according to claim 1, characterized in that: The R1 and R2 are each independently selected from H, a C1-C6 substituted or unsubstituted alkyl group.
3. The packaging film according to claim 2, characterized in that: The R1 and R2 are each independently selected from any one or more of H, methyl, ethyl, propyl, isopropyl, pentyl, and hexyl.
4. The packaging film according to claim 3, characterized in that: The R1 and R2 are each independently selected from any one of H, methyl or ethyl.
5. The packaging film according to claim 1, characterized in that: The active agent is selected from any one or more of ethylene glycol, 1,2-butanediol, ethylenediamine, and adipoyl chloride.
6. The packaging film according to claim 1, characterized in that: The M n+ Selected from Na + , K + Any one or more of .
7. The packaging film according to claim 1, characterized in that: The light transmittance of the enhancement layer is greater than 85%.
8. The packaging film according to claim 7, characterized in that: The thickness of the reinforcement layer is between 0.10 and 0.55 mm.
9. The packaging film according to claim 7, characterized in that: The melting point of the matrix resin is 80-110°C.
10. The packaging film according to claim 1, characterized in that: The thickness of the first adhesive layer and the second adhesive layer are independently 0.05-0.4 mm, and the first adhesive layer and the second adhesive layer are independently composed of: 100 parts by weight of base resin; 0.1-2 parts by weight of initiator; 0.2 to 2 parts by weight of a bridging agent; and 0.05~1 parts by weight of silane coupling agent.
11. The packaging adhesive film according to claim 10, characterized in that: The matrix resin is selected from any one or more of ethylene vinyl acetate copolymer, ethylene propylene copolymer, ethylene butene copolymer, ethylene pentene copolymer, ethylene hexene copolymer and ethylene octene copolymer.
12. The packaging film according to claim 10, characterized in that: The initiator is selected from tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy) ) butane, tert-amyl peroxy 2-ethylhexyl carbonate, 2,5-dimethyl 2,5-dimethyl 2,5-dimethyl 2,5-bis(benzoylperoxy)-hexane, tert-amyl peroxy carbonate, tert-butyl peroxy 3,3,5-trimethylhexanoate, azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride, azoisobutylcyanoformamide, any one or more thereof.
13. The packaging adhesive film according to claim 10, characterized in that: The bridging agent is selected from triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate Acid ester, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, 2,4,6-tris(2-propenyloxy)-1,3,5-triazine, tricyclohexane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, any one or more thereof.
14. The packaging film according to claim 10, characterized in that: The silane coupling agent is selected from any one or more of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl triperoxide tert-butyl silane, vinyl triacetoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-glycidyloxypropyl trimethylsilane, and 3-aminopropyl trimethylsilane.
15. The packaging adhesive film according to claim 10, characterized in that: The first bonding layer and the second bonding layer each independently include 0.5 to 20 parts of a pigment.
16. The packaging adhesive film according to claim 15, characterized in that: The pigment is selected from any one or more of titanium dioxide, carbon black, copper chrome black, iron oxide red and iron oxide yellow.
17. The packaging adhesive film according to claim 10, characterized in that: The first adhesive layer and the second adhesive layer each independently include 0.5 to 2 parts of an ultraviolet absorber. 18 . A composite glass, comprising a first glass, an adhesive film and a second glass stacked in sequence, wherein the adhesive film is selected from the encapsulation adhesive film according to any one of claims 1 to 17.
19. A photovoltaic building integrated assembly, comprising a packaging film, characterized in that: The packaging film is the packaging film according to any one of claims 1 to 17.
Citation Information
Patent Citations
Packaging adhesive film and preparation method thereof
CN111334200A
Packaging material, related coating and preparation method thereof, and photovoltaic module
CN111675971A